When Autonomy Conflicts with Harm Preventionts with Harm Prevention - Mazza, Oscar M. (Revista del Hospital Italiano de Buenos Aires, 2026)
Can a person with mild cognitive impairment make decisions about their own medical care? The editors of the Revista del Hospital Italiano de Buenos Aires invited two distinguished experts to reflect on a hypothetical clinical scenario. Dr. Oscar Mazza examines how to balance autonomy, beneficence, and protection in people with mild cognitive impairment, and discusses the roles of the family, the healthcare team, and advance directives. Read Dr. F. Giber’s commentary: [link]